Social media management : - Looy, Amy Van (Springer, 2016)
This undergraduate textbook adopts the perspective of organizations - not individuals - and clarifies the impact of social media on their different departments or disciplines, while also exploring how organizations use social media to create business value. To do so, the book pursues a uniquely multi-disciplinary approach, embracing IT, marketing, HR and many other fields. Readers will benefit from a comprehensive selection of current topics, including: tools, tactics and strategies for social media, internal and external communication, viral marketing campaigns, social CRM, employer branding, e-recruiting, search engine optimization, social mining, sentiment analysis, crowdfunding, and legal and ethical issues.